Comparison of lithium‐ion battery cell technologies applied in the regenerative braking system. Issue 4 (26th September 2022) - Nazir, Mian Hammad; Rahil, Abdulla; Partenie, Eduard; Bowkett, Mark; Khan, Zulfiqar A.; Hussain, Muhammad M.; Zaidi, Syed Zohaib J.
Abstract: This research presents the performance evaluation of four various types of top‐of‐the‐line commercial and prototype lithium‐ion energy storage technologies with an objective to find out the optimal cell technology, which is suitable for the development of high power battery packs for regenerative braking systems applied in next‐generation demonstrator platform vehicles. The novel porotype lithium‐ion cell technology is developed using linear combined nanofibers and microfibers battery separators laden utilizing wet nonwoven processes compared to the dry process laden multilayered porous film separators in commercial cell technologies. The performance comparison of all technologies has been conducted both at "cell‐level" and "pack level" through the study of internal performance parameters, such as capacity, resistance, self‐discharge, and battery temperature rise. This study also encompasses the differences in using external pack assembly and/or development parameters like the number of cells which are required to develop the pack, pack mass, pack volume, and pack cost. Both the internal performance parameters and external pack assembly and development parameters have revealed that novel prototype cell technology is the most optimal technology among all four cell technologies for regenerative braking systems, which have been investigated during this research. The novelty of this work is the development of novel prototype cell technology and its performance comparison with commercially available cell technologies used in regenerative braking systems of the latest hybrid/electric vehicles, which is in line with global initiatives, such as UK/EU transition to EVs and UN sustainability goals. The significance of this work in terms of high power pack development for regenerative braking of next‐generation vehicles is evident from various industrial applications. This work will influence decisions for both battery testing techniques and accurate battery comparison methods for automotive, locomotive, aerospace, battery manufacturers, and wind turbine industries. Abstract : This research presents the performance evaluation of four various types of top‐of‐the‐line commercial and prototype lithium‐ion energy storage technologies with the objective to find out the optimal cell technology suitable for the development of high‐power battery packs for regenerative braking systems applied in next‐generation demonstrator platform vehicles. The novelty of this work is the development of novel prototype cell technology and its performance comparison with commercially available cell technologies used in the regenerative braking systems of the latest HEVs in line with the low carbon global initiatives.